PERBANDINGAN KADAR FLAVONOID TOTAL EKSTRAK ETANOLIK DAUN BELUNTAS (Pluchea indica L.) BERDASARKAN VARIASI KONSENTRASI PELARUT SECARA SPEKTROFOTOMETER UV–VIS - Danang Yulianto; Selvi Ratna Savitri (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2019)
Background: Testing or analysis of total flavonoid levels of herbal ethanolic extract of beluntas (Pluchea indica L.) leaves has been carried out. Beluntas leaf (Pluchea indica L.) is a traditional medicinal plant that is not widely known by the public about its benefits for various diseases.Objective: to determine an overview of total flavonoid levels between different of variation concentration.Method:Extraction of the compound of beluntas (Pluchea indica L.) leaves was carried out by maceration method using 100 mL of aquadest and 100 mL of ethanol - aquades mixture withethanol96% (v / v) concentrations, ethanol 70% (v / v), ethanol 50% (v / v), and ethanol 30% (v / v) for 24 hoursrespectively. Phytochemical screening continued with Thin Layer Chromatography (TLC). While the measurement of the levels of flavonoid compounds in the sample was conducted out by the UV-Vis spectrophotometer methodResult:Phytochemical screening using TLC on beluntas (Pluchea indica L.) leaves is known to contain flavonoidsrespectively. The measurement results of total flavonoids in aquadest extract amounted to 1.94% (b / b), whereas in ethanol extract 96% -aquadest was 16.62% (b / b), ethanol extract - aquadest 70% by 33.80% (b / b), 50% ethanol - aquades was 30.29% (b / b) and 30% ethanol - aquades was 15.27% (b / b). The results of measurements of total flavonoid levels in beluntas (Pluchea indica L.) leaves stated that the highest total flavonoid content obtained in 70% ethanol extract was 33.80% (b / b), followed by 50% ethanol was 30.29% (b / b), 96% ethanol 16.62% (b / b), 30% ethanol was 15.27% (b / b), and 30% distilled water was 1, 94% (b / b).